Retail and Marketing Channels: Economic and Marketing Perspectives on Producer-Distributor Relationships - PELLEGRINI, Luca (Institutional Knowledge at Singapore Management University, 1989)
Selected papers from the Fourth International Conference on Distribution, held at Bocconi University, Milan, July 3-4, 1987, organized by the Centro di studi sul commercio and the Dept. of Marketing of New York University.